Analysis of the Use of Banksy Image in Improving Students’ Writing Skills - Muhamad Sofian Hadi; Lidiyatul Izzah; Azhar Dwiyan Putra (Universitas Pendidikan Mandalika, 2021)
This study aims to improve students’ Writing abilities using Bansky Image. The method used in research is a quantitative method with Pre Experimental as a research design. Both pre-test and post-test used as the instruments in collecting the data. The writer used one classes of the tenth grade of MA Al Fathiyah, Jakarta Timur, for the population. The sampling technique used was cluster sampling, in which one class was determined as experimental and the control class. The data was analyzed statistically by using a t-test. The result of this analysis indicated that the average value of the students was 75.7, the statistical calculation showed that the results of to (t-observation)> tt (t-table) in which to obtained was 25.357 while the value of tt was 2.037 with a significant level of 5% (0.05), since, to was higher than tt. Therefore alternative hypothesis (Ha) was accepted while null hypothesis was rejected. From these analysis results, this research summarized that Banksy Image was an effective medium to improve students’ Writing skills.